Supercomputing Frontiers 4th Asian Conference, SCFA 2018, Singapore, March 26-29, 2018, Proceedings - Yokota, Rio; Wu, Weigang (Theoretical Computer Science and General Issues, 2018)
It constitutes the refereed proceedings of the 4th Asian Supercomputing Conference, SCFA 2018, held in Singapore in March 2018. Supercomputing Frontiers will be rebranded as Supercomputing Frontiers Asia (SCFA), which serves as the technical programme for SCA18. The technical programme for SCA18 consists of four tracks: Application, Algorithms & Libraries Programming System Software Architecture, Network/Communications & Management Data, Storage & Visualisation The 20 papers presented in this volume were carefully reviewed nd selected from 60 submissions.